Evaluation of aerial thermography to discriminate loft insulation in residential housing - Allinson, David (2007)
This thesis examines the use of aerial thermography data to discriminate loft (attic) insulation levels in residential housing, with ventilated pitched roofs, in the UK. Quantitative techniques from the fields of remote sensing, GIS, building physics and atmospheric science were used to develop a methodology and analyse survey data flown over Nottingham in 2001.